2019
DOI: 10.1101/709642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Movement and performance predict widespread cortical activity in a visual detection task

Abstract: Recent studies in mice reveal widespread cortical signals during task performance, however the various task-related and task-independent processes underlying this activity are incompletely understood. Here we recorded wide-field neural activity, as revealed by GCaMP6s, from dorsal cortex while simultaneously monitoring orofacial movements, walking, and arousal (pupil diameter) of head-fixed mice performing a Go/NoGo visual detection task and examined the ability of task performance and spontaneous or task-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Cortical state fluctuations have dramatic consequences for the processing of sensory information and the execution of sensoryguided behavior. State fluctuations in mice have traditionally been studied in the context of stillness versus locomotion, though several recent studies have begun to uncover the functional properties of state changes that occur in the absence of locomotion (Reimer et al, 2014;McGinley et al, 2015a,b;Vinck et al, 2015;Salkoff et al, 2019;Stringer et al, 2019). Our results provide an account of how sensory neuronal responsiveness in mouse V1 and visual detection performance vary as a continuous function of arousal.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Cortical state fluctuations have dramatic consequences for the processing of sensory information and the execution of sensoryguided behavior. State fluctuations in mice have traditionally been studied in the context of stillness versus locomotion, though several recent studies have begun to uncover the functional properties of state changes that occur in the absence of locomotion (Reimer et al, 2014;McGinley et al, 2015a,b;Vinck et al, 2015;Salkoff et al, 2019;Stringer et al, 2019). Our results provide an account of how sensory neuronal responsiveness in mouse V1 and visual detection performance vary as a continuous function of arousal.…”
Section: Discussionmentioning
confidence: 67%
“…Mice were given ϳ2 h to recover from anesthesia before behavioral testing. We have previously shown that this volume of muscimol injection inactivates ϳ1 mm 2 of cerebral cortex, without inactivation of surrounding areas (Salkoff et al, 2019).…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…In this case, task-evoked neural responses would occur on top of physiological statedependent patterns of ongoing activity (Arieli et al, 1996). Alternatively, ongoing activity could reflect other variables such as arousal or motor actions (Musall et al, 2019;Salkoff et al, 2019;Stringer et al, 2019).…”
Section: Putative Representation Of Thirst State In Ongoing Insctx Acmentioning
confidence: 99%